Microwave Vacuum Drying Variables Affecting to Processing of Dried Gomphrena globosa Floral - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Microwave vacuum drying is one of the most energy demanding processes. Water evaporation takes place at lower temperatures under vacuum, and hence the product processing temperature can be significantly lower, offering higher product quality. Gomphrena globosa is one of the traditional medicinal plants widely distributed in Vietnam. It’s considered as a valuable source for pharmaceuticals against various ailments. Gomphrena globosa L. flowers are a promising source of natural antioxidants. Objective of this study focused on the influence of processing parameters such as the microwave power (100, 150, 200, 250, 300 W), system pressure (20, 25, 30, 35, 40 kPa) and drying time (15, 20, 25, 30, 35 min) on shrinkage coefficient, rehydration ratio, color change, total phenolic, flavonoid, betacyanin of dried herbal during the microwave vacuum (MV) drying of Gomphrena globosa. At the end of drying process, we also monitored the stability of dried Gomphrena globosa flower during 12 months of preservation. Our results showed that the optimal drying process should be conducted at microwave power 250 W at 35 kPa within 30 min to get the best quality of dried Gomphrena globosa flower. From this approach, shelf-life of dried Gomphrena globosa flower could be last for 12 months without any deterioration. The low temperature and fast mass transfer conferred by vacuum combined with rapid energy transfer by microwave heating generates very rapid, low temperature drying and thus it has the potential to improve energy efficiency and product quality.Keywords: Gomphrena globosa, microwave vacuum drying, Shrinkage coefficient, Rehydration ratio, Color change, Total phenolic, Flavonoid, Betacyanin.